Can OHADA Increase Legal Certainty in Africa? - Beauchard, Renaud; Kodo, Mahutodji Jimmy Vital (World Bank, Washington, DC, 2014)
This paper describes the origins, structure, and practical impact of the Organization for the Harmonization of Business Law in Africa (OHADA). It analyzes the institutional framework created via the OHADA treaty and the legal, jurisprudential, and functional challenges that OHADA member states are still grappling with. Details of the nine substantive laws that have so far been ratified as uniform acts by means of the treaty have also been provided. The authors conclude that in making OHADA law effective, member states face continuing and substantial resource deficits, institutional deficiencies, language ambiguities, and intransigent official attitudes toward the need for appropriate mechanisms for the pursuance and enforcement of OHADA laws and processes.